The Effect of Infrastructure Development and Government Expenditures in Social Services to Poverty Reduction of Lao PDR - phanthavong, chanthakhon; HER, Pheng; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
Poverty problem is still challenging for Lao PDR’s development, the objective of this study is to analyze the role of infrastructure and government spending in social services (education and health care) on poverty reduction during 2006-2024. Based on the Auto Regressive Distributed Lag approach, we examine both the short and long run relationships linking total road length, spending on education and health by government, and poverty (proxied by people with IWI under 50%). The findings reveal robust long-run cointegration relationships among the variables, thus verifying heterogeneity in infrastructure and social outlay jointly determining poverty reduction. The results imply that the long-run effect of infrastructure development on poverty is significantly negative, indicating road network improvement increases market access, economic welfare and quality of life. Education spending also has the expected negative sign, being statistically non-significant; showing that its poverty reducing benefits are a long-term process via human capital accumulation. On the other hand, health expenditure is positively associated with poverty in short-term, which might be indicating temporary reallocation of fiscal resources during crisis (e.g., COVID-19). All diagnostic tests verify that the model is stable, normally distributed and does not have serial correlation or heteroskedasticity, which ensures the validity of test results. Overall, the study argues that continued investment in infrastructure and welfare-enhancing social allocations will be crucial to generate inclusive and sustainable poverty reduction in Lao PDR. Policy implications underscore the importance of good fiscal management, improving education and healthcare quality, and maintenance on existing infrastructure to achieve efficient development. The findings enrich empirical support for combining infrastructure-led and human capital development approaches in poverty alleviation strategies